2012
DOI: 10.1292/jvms.12-0035
|View full text |Cite
|
Sign up to set email alerts
|

Successful Induction of Lactation in a Barren Thoroughbred Mare: Growth of a Foal Raised on Induced Lactation and the Corresponding Maternal Hormone Profiles

Abstract: ABSTRAcT. The purpose of this study was to demonstrate that a barren parous Thoroughbred mare with lactation induced by hormonal treatment can be introduced to an orphan foal at the same farm and that the mare can become pregnant after the end of the hormonal treatment. An additional purpose was to investigate the changes in the plasma concentrations of prolactin, estradiol-17β, progesterone, folliclestimulating hormone, and luteinizing hormone before, during, and after hormonal treatment. The difference in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The results support the hypothesis of previous [1,2] and recent [3] studies, which showed that the sudden increase of circulating PRL concentrations, as observed in healthy pregnancy of pony and Thoroughbred mares, could be the trigger for the onset of lactation also in Ragusana mares.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results support the hypothesis of previous [1,2] and recent [3] studies, which showed that the sudden increase of circulating PRL concentrations, as observed in healthy pregnancy of pony and Thoroughbred mares, could be the trigger for the onset of lactation also in Ragusana mares.…”
Section: Discussionsupporting
confidence: 91%
“…Circulating PRL concentrations obtained in jennies (Equus asinus) are in agreement with data obtained in control mares (Equus caballus) but were lower than those observed during sulpiride treatment, with superimposable milk production [3,20].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations